Integration of Multiplex Bead Assays for Parasitic Diseases into a National, Population-Based Serosurvey of Women 15-39 Years of Age in Cambodia. - Jeffrey W Priest; M Harley Jenks; Delynn M Moss; Bunsoth Mao; Sokhal Buth; Kathleen Wannemuehler; Sann Chan Soeung; Naomi W Lucchi; Venkatachalam Udhayakumar; Christopher J Gregory; Rekol Huy; Sinuon Muth; et al. (Public Library of Science (PLoS), 2016)
Collection of surveillance data is essential for monitoring and evaluation of public health programs. Integrated collection of household-based health data, now routinely carried out in many countries through demographic health surveys and multiple indicator surveys, provides critical measures of progress in health delivery. In contrast, biomarker surveys typically focus on single or related measures of malaria infection, HIV status, vaccination coverage, or immunity status for vaccine-preventable diseases (VPD). Here we describe an integrated biomarker survey based on use of a multiplex bead assay (MBA) to simultaneously measure antibody responses to multiple parasitic diseases of public health importance as part of a VPD serological survey in Cambodia. A nationally-representative cluster-based survey was used to collect serum samples from women of child-bearing age. Samples were tested by MBA for immunoglobulin G antibodies recognizing recombinant antigens from Plasmodium falciparum and P. vivax, Wuchereria bancrofti, Toxoplasma gondii, Taenia solium, and Strongyloides stercoralis. Serologic IgG antibody results were useful both for generating national prevalence estimates for the parasitic diseases of interest and for confirming the highly focal distributions of some of these infections. Integrated surveys offer an opportunity to systematically assess the status of multiple public health programs and measure progress toward Millennium Development Goals.